Dual-Action Icariin-Containing Thermosensitive Hydrogel for Wound Macrophage Polarization and Hair-Follicle Neogenesis - Teng, Ying-Ying; Zou, Ming-Li; Liu, Si-Yu; Jia, Yuan; Zhang, Kai-Wen; Yuan, Zheng-Dong; Wu, Jun-Jie; Ye, Jun-Xing; Yu, Shun; Li, Xia; Zhou, Xiao-Jin; Yuan, Feng-Lai (Frontiers in Bioengineering and Biotechnology, 2022)
Bone morphogenetic protein (BMP) pathway is essential for M2 macrophage polarization and hair-follicle neogenesis. Icariin, a flavonoid derived from Epimedium, is a mediator of the BMP pathway. Here, we develop a hydrogel formulation functionalized with icariin for regulation of macrophage polarization to accelerate wound healing and hair-follicle neogenesis. Compared to skin defects without icariin treatment, those treated with icariin+PEG hydrogel healed faster and had new hair follicles. Results in vivo showed that icariin+PEG hydrogel induced a higher level of M2 phenotypic transformation of macrophages. Moreover, icariin+PEG hydrogel significantly accelerated wound-repair process by reducing the invasion of inflammation, excessive deposition of collagen, immoderate activation of myofibroblasts, and increasing the regeneration of hair follicles. Furthermore, studies in vitro demonstrated that the icariin+PEG hydrogel induced macrophages to polarize to the M2 phenotype and dermal papilla cell to hair follicles. Finally, molecular analysis demonstrated that the icariin+PEG hydrogel increased the expression of BMP4 and Smad1/5 phosphorylation in skin wounds. These results demonstrate the therapeutic potential of icariin-containing thermosensitive hydrogels for inducing M2 macrophage polarization to accelerate wound healing and promote hair-follicle neogenesis by regulating the BMP pathway.